Reno-Gonadal Venous Anastomosis for Right Renal Venous Drainage Following Juxtarenal Cavectomy for Renal Cell Carcinoma (Journal of Kidney Cancer, 2025)
This article is a case report of a 62-year-old male with a left-sided renal cell carcinoma (RCC) with a level II inferior vena cava (IVC) thrombus and caval occlusion. He was managed with open left radical nephrectomy and juxtarenal cavectomy. To preserve right renal venous drainage, the right renal vein was anastomosed to the right gonadal vein. He has not had any renal functional decline or disease recurrence with 3 years of follow-up. The focus of this article is to discuss this distinctive method for vascular reconstruction as an option for right renal venous drainage following left nephrectomy and juxtarenal cavectomy.